ALUMINIC-RARE-EARTH-PRECIOUS METALS FORMATION IN NEPHELINE SYENITES OF ARMENIA (Proceedings of the YSU C: Geological and Geographical Sciences, 2011)
Nepheline syenites of Armenia which are the potential raw stock base of the aluminum industry, soda products and cement production must be considered as a complex multipurpose raw stock with prospects of rear-earth and fine precious metals mineralization.
Keywords: nepheline; Nepheline syenites; aluminic-rare-earth-precious metals formation